2021
DOI: 10.31274/tcse.11524
|View full text |Cite
|
Sign up to set email alerts
|

“I’d Say I Have a Bit of Work to Do”: Exploring Elementary Social Studies Pre-Service Teacher Criticality through PhotoVoice

Abstract: Elementary pre-service teacher education offers important insights in terms of how teachers understand and develop criticality surrounding self-reflexivity, interaction with social studies content, and pedagogy. This study applied critical self-authorship frameworks, Freire's theory of conscientisation, and PhotoVoice methodology to explore pre-service teachers' self-awareness of their developing professional identities as situated within an elementary social studies methods course. Broadly, the study explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Through photovoice, youth and community members were able to develop antiracist storytelling for social justice and build their community's capacity to challenge their conditions and address their identified problems. Stanton and Hancock ( 2021 ) used photovoice to evaluate and cultivate the critical consciousness and antiracist/anticolonial pedagogy of preservice elementary social studies teachers. They found that these teachers needed greater sustained engagement during preservice teacher training with opportunities to develop critical antiracist consciousness, self‐definition as teachers, and self‐transformation as teachers of social justice and that photovoice projects can provide such opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Through photovoice, youth and community members were able to develop antiracist storytelling for social justice and build their community's capacity to challenge their conditions and address their identified problems. Stanton and Hancock ( 2021 ) used photovoice to evaluate and cultivate the critical consciousness and antiracist/anticolonial pedagogy of preservice elementary social studies teachers. They found that these teachers needed greater sustained engagement during preservice teacher training with opportunities to develop critical antiracist consciousness, self‐definition as teachers, and self‐transformation as teachers of social justice and that photovoice projects can provide such opportunities.…”
Section: Introductionmentioning
confidence: 99%